Assessing and addressing literacy needs cases and instructional strategies - Combs, Barbara; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 2012)
Designed to help preservice & inservice teachers understand the problems that children encounter when learning to read, this text provides key instructional strategies related to best practices in literacy instruction. The text promotes reflection & analysis that will provoke thoughtful responses & discussions.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Reading -- Remedial teaching; Reading -- Ability testing; Reading teachers -- Training of; Electronic books